2018
DOI: 10.1007/s11367-018-1436-x
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for effects of carbon flows in LCA of biomass-based products—exploration and evaluation of a selection of existing methods

Abstract: Purpose Life cycle assessment (LCA) has become one of the most widespread environmental assessment tools during the last two decades. However, there are still impacts that are not yet fully integrated, including climate impacts of land use. This study contributes to the development process by testing a selection of recently proposed climate impacts assessment methods, some more focused on the impact of land use and others more focused on a product's carbon life cycle. Methods Several assessment methods have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…Peter et al [6] used the IPCC inventory and modeling methods to calculate the carbon footprint of agricultural products. The research of Liptow et al [7] based on the life cycle theory, used the recently proposed climate impact assessment method to evaluate biological basic products, and discuss carbon emissions during different life cycles. Some scholars used the IPCC method to estimate the total carbon emissions of various provinces in China [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Peter et al [6] used the IPCC inventory and modeling methods to calculate the carbon footprint of agricultural products. The research of Liptow et al [7] based on the life cycle theory, used the recently proposed climate impact assessment method to evaluate biological basic products, and discuss carbon emissions during different life cycles. Some scholars used the IPCC method to estimate the total carbon emissions of various provinces in China [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of land use and carbon cycle impacts have a profound effect on the results. 51 The impact of biogenic CO 2 and the secondary effect of soil organic carbon/land-use change are excluded in the generalised system boundary reviewed by Patel et al 52 as well as Sunde et al 53 for the woody biomass to liquid production. It should be taken note that the purpose of the table is to highlight the inconsistency rather than to comment on the comprehensiveness of the assessment.…”
Section: Overview Of Direct and Secondary Carbon Emission Footprintmentioning
confidence: 99%
“…Similar issue on the biogenic carbon neutrality assumption has been discussed by Wiloso et al 33 The inconsistency is also illustrated through the selected studies in Table 2. Liptow et al 51 identified the same issue as well where the carbon flows in LCA are not fully integrated. The inclusion of land use and carbon cycle impacts have a profound effect on the results 51 .…”
Section: Overview Of Direct and Secondary Carbon Emission Footprintmentioning
confidence: 99%
See 1 more Smart Citation
“…The study focused on three categories or indicators namely the techno-economic, environmental, and social impacts. Liptow et al [10] accounted for the effect of carbon flows in LCA of biomass-based products considering the case of Sweden for wood to ethylene and Brazil for sugarcane to ethylene via different routes. The global warming potentials and land use impacts were the analyzed indicators in the life-cycle.…”
mentioning
confidence: 99%